Theoretical study on composition‐dependent properties of ZnO·nAl2O3 spinels. Part I: Optical and dielectric. Issue 10 (17th March 2021) - Xu, Pengyu; Wang, Hao; Ren, Lu; Tu, Bingtian; Wang, Weimin; Fu, Zhengyi
Abstract: Due to the transparency for both light and radio waves, Zn‐Al spinels (ZnO· n Al2 O3 ) may be applied as multi‐mode windows. The rules of cation distribution in ZnO· n Al2 O3 were determined with in‐depth analysis of the local structure and then restricted by these rules, reasonable Zn16–6 x Al32+4 x O64 ( x  = 0.0, 0.5, 1.0, 1.5, 2.0) supercells were constructed to explore the composition‐dependence of properties via the first‐principles calculations. Based on the insights into the crystal, bond, electronic, and phonon structures, the effect of the cation substitution on the light absorption in ultraviolet and infrared wavelengths, refractive index, and dispersion in the visible region as well as the dielectric constant and dielectric loss in the microwave band was disclosed. The d−p hybridization of Zn and O results in a lower refractive index and a higher Abbé number of ZnO· n Al2 O3 at larger n . Since Al IV ions are lighter and form stronger bonds with O 2− than Zn IV ions, the ultraviolet and infrared cut‐off of the transmission window are red‐shifted and blue‐shifted with rising n, respectively. Al IV ions are insignificant contributors to the low‐frequency vibration modes, therefore the dielectric loss weakens as n increases. The understandings are significant for not only customizing the composition of ZnO· n Al2 O3 but also designing novel oxide spinels with desired optical and dielectric properties.